2021
DOI: 10.3390/cells10071642
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy, Apoptosis, the Unfolded Protein Response, and Lung Function in Idiopathic Pulmonary Fibrosis

Abstract: Autophagy, apoptosis, and the unfolded protein response (UPR) are fundamental biological processes essential for manifold cellular functions in health and disease. Idiopathic pulmonary fibrosis (IPF) is a progressive and lethal pulmonary disorder associated with aging that has limited therapies, reflecting our incomplete understanding. We conducted an observational study linking molecular markers of cell stress response pathways (UPR: BiP, XBP1; apoptosis: cleaved caspase-3; autophagy: LC3β) in lung tissues fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 63 publications
1
33
0
Order By: Relevance
“…To simplify the analysis, we collapsed the BioInt units (dots) presenting a Wang's Semantic similarity coefficient >0.6 into functional clusters (top 10 largest clusters are arranged in Y axes). In particular, the BioInt units most targeted by fibrosis-related DEg in lung included membrane permeability, proteolysis and apoptosis signaling-related functions [35] . In the case of psoriasis, stress-related protein folding and degradation-regulatory pathways were consistently altered in immune-related organs [39] .…”
Section: Resultsmentioning
confidence: 99%
“…To simplify the analysis, we collapsed the BioInt units (dots) presenting a Wang's Semantic similarity coefficient >0.6 into functional clusters (top 10 largest clusters are arranged in Y axes). In particular, the BioInt units most targeted by fibrosis-related DEg in lung included membrane permeability, proteolysis and apoptosis signaling-related functions [35] . In the case of psoriasis, stress-related protein folding and degradation-regulatory pathways were consistently altered in immune-related organs [39] .…”
Section: Resultsmentioning
confidence: 99%
“…TMA slides (5-µm thick) were deparaffinized in 60 °C for 30min and subsequently rehydrated in Xylene with a gradient alcohol series. Heat-mediated antigen retrieval (0.01 M sodium citrate buffer, pH 6.0) was performed as described previously [ 22 , 26 , 27 ]. In order to eliminate background interference, the slides were washed with Phosphate buffered saline (PBS) and blocked with blocking solution (1.5 mL Maleic Acid Buffer, 0.5 mL FBS, 0.5 mL stock blocking solution, 50 µL 10% Tween-20 and 2.5 mL PBS) at room temperature for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…It maintains the homeostasis of the intracellular environment by forming autophagosome vesicles, engulfing dysfunctional cytoplasm and organelles, and forming autolysosomes to degrade the contents of vesicles (89,90). Autophagy disorder involves various diseases, also including IPF (91)(92)(93)(94)(95)(96). Accumulating evidence revealed that autophagy activity was impaired in IPF, and inhibition of autophagy could induce myofibroblast proliferation and ECM deposition, thus leading to fibrosis (97,98).…”
Section: Autophagymentioning
confidence: 99%